Encapsulation of Metal Nanoparticle Catalysts Within Mesoporous Zeolites and Their Enhanced Catalytic Performances: A Review - Xu, Dongdong; Lv, Hao; Liu, Ben (Frontiers in Chemistry, 2018)
Metal nanoparticles (NPs) exhibit desired activities in various catalytic reactions. However, the aggregation and sintering of metal NPs usually cause the loss of catalytic performance in practical reaction processes. Encapsulation of catalytically active metal NPs on/within a high-surface-area inorganic support partially resolve such concerns. Microporous zeolites, owing to their rigid frameworks and porous structural features, have been considered as one of ideal inorganic supports. Metal NPs can be easily encapsulated and stabilized within zeolitic frameworks to prevent unwished aggregation during the catalysis. Unfortunately, sole microporous nanochannels (generally <1 nm) in conventional zeolites are not easy to be accessed. The introduction of another set of nanochannel (e.g., mesopore), known as mesoporous zeolites, can greatly improve the mass-transfer efficiency, which is structurally beneficial for most catalytic reactions. The coexistence of micropores and mesopores in inorganic supports provides the synergetic advantages of both fine confinement effect for metal NPs and easy diffusion for organic reactants/intermediates/products. This review focuses on the recent advances in the design and synthesis of mesoporous zeolites-encapsulated metal NP catalysts as well as their desired catalytic performances (activity and stability) in organic reactions. We first discuss the advantages of mesoporous zeolites as the supports and present general strategies for the construction of mesoporous zeolites. Then, the preparation methods on how to encapsulate NP catalysts within both microporous and mesoporous zeolites are clearly demonstrated. Third, some recent important cases on catalytic applications are presented to verify structural advantages of mesoporous zeolite supports. Within the conclusion, the perspectives on future developments in metal NP catalysts encapsulated within mesoporous zeolites are lastly discussed.